Design and Numerical Analysis of Mid-Size Horizontal Axis Wind Turbine Blade for Kagbeni, Nepal - Lamsal, Gaurav; Pandey, Aayus; Chhetri, Ashim; Dharel, Bijaya; Subedi, Nishan; Awasthi, Pawan C.; Karki, Dipesh (Journal of Engineering and Sciences, 2025)
This study presents the aerodynamic design and steady-state CFD validation of a 100kW horizontal-axis wind turbine blade using NREL-S series airfoils, optimized for wind conditions in Kagbeni. The region's reliable and strong wind potential offers promising scope for clean energy generation, particularly in off-grid communities. This study addresses the critical need for site-specific turbine designs by optimizing a mid-size HAWT blade for high-altitude, low-density atmospheric conditions in Kagbeni, Nepal, enhancing local renewable energy potential. The blade geometry was generated in QBlade using site-specific wind data from the Global Wind Atlas and then exported in SolidWorks for CFD analysis. Steady-state RANS simulations were performed in ANSYS Fluent using the SST k–ω turbulence model with a sliding mesh approach of two zones. Mesh convergence was achieved at 4.47 million cells with a torque difference of less than 0.5%. At a tip speed ratio λ = 7 and a rotational speed of 42 RPM, the rotor produced a torque of 32,612.8Nm and a power output of 143.8kW, corresponding to a power coefficient of Cp = 0.280. The study contributes to developing region-specific wind energy solutions for high-altitude sites.